Depression, posttraumatic stress and relationship distress in parents of very preterm infants - Winter, L.; Colditz, P.; Sanders, M.; Boyd, Roslyn; Pritchard, M.; Gray, P.; Whittingham, K.; Forrest, K.; Leeks, R.; Webb, L.; Marquart, L.; Taylor, K.; et al. (Springer, 2018)
To determine the prevalence, associated factors, and relationships between symptoms of depression, symptoms of posttraumatic stress (PTS), and relationship distress in mothers and fathers of very preterm (VPT) infants ( < 32 weeks). Mothers (n = 323) and fathers (n = 237) completed self-report measures on demographic and outcome variables at 38 days (SD = 23.1, range 9–116) postpartum while their infants were still hospitalised. Of mothers, 46.7% had a moderate to high likelihood of depression, 38.1% had moderate to severe symptoms of PTS, and 25.1% were in higher than average relationship distress. The corresponding percentages in fathers were 16.9, 23.7, and 27%. Depression was positively associated with having previous children (p = 0.01), speaking little or no English at home (p = 0.01), financial stress (p = 0.03), and recently accessing mental health services (p = 0.003) for mothers, and financial stress (p = 0.005) and not being the primary income earner (p = 0.04) for fathers. Similar associations were found for symptoms of PTS and relationship distress. Being in higher relationship distress increased the risk of depression in both mothers (p < .001) and fathers (p = 0.03), and PTS symptoms in mothers (p = 0.001). For both mothers and fathers, depression was associated with more severe PTS symptoms (p < .001). Fathers of VPT infants should be screened for mental health problems alongside mothers, and postpartum parent support programs for VPT infants should include strategies to improve the couple relationship.